2020
DOI: 10.1093/ajcn/nqz344
|View full text |Cite
|
Sign up to set email alerts
|

Reformulation initiative for partial replacement of saturated with unsaturated fats in dairy foods attenuates the increase in LDL cholesterol and improves flow-mediated dilatation compared with conventional dairy: the randomized, controlled REplacement of SaturatEd fat in dairy on Total cholesterol (RESET) study

Abstract: Background Modifying dairy fat composition by increasing the MUFA content is a potential strategy to reduce dietary SFA intake for cardiovascular disease (CVD) prevention in the population. Objectives To determine the effects of consuming SFA-reduced, MUFA-enriched (modified) dairy products, compared with conventional dairy products (control), on the fasting cholesterol profile (primary outcome), endothelial function assessed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
59
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(61 citation statements)
references
References 48 publications
2
59
0
Order By: Relevance
“…Although debatable, chronic consumption of diets with a high ratio of saturated to unsaturated fatty acids (SFA diets) increases body adiposity, impairs glucose homeostasis, raises the cardiovascular risk, and reduces the healthy disease-free life span in animals and humans ( 1 , 2 ). These diets negatively affect the proper secretion and action of key hormones—insulin, leptin, and adiponectin—underlying metabolic homeostasis and energy balance ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Although debatable, chronic consumption of diets with a high ratio of saturated to unsaturated fatty acids (SFA diets) increases body adiposity, impairs glucose homeostasis, raises the cardiovascular risk, and reduces the healthy disease-free life span in animals and humans ( 1 , 2 ). These diets negatively affect the proper secretion and action of key hormones—insulin, leptin, and adiponectin—underlying metabolic homeostasis and energy balance ( 3 ).…”
Section: Introductionmentioning
confidence: 99%
“…Most recently, Vasilopoulou et al (2020) examined the impact of modified dairy fat consumption, through the provision of products with modified monounsaturated fatty acid (MUFA) content in adults at moderate CVD risk—the RESET study (controlled REplacement of SaturatEd fat in dairy on Total cholesterol). The authors concluded that consumption of a high-fat diet containing modified dairy products with reduced saturated fatty acids, and enriched monounsaturated fatty acids showed beneficial effects on fasting LDL cholesterol and endothelial function compared with conventional dairy products [ 47 ]. Finally, although not an intervention study, Drouin-Chartier (2019), recently examined dairy intake and risk of diabetes, and reported positive impacts for yoghurt and reduced-fat milk, but a negative association for cheese [ 48 ].…”
Section: Dairy Fat and The Link To Healthmentioning
confidence: 99%
“…It has been suggested that the use of such traditional markers alone may limit the ability to predict health outcomes from the fat in dairy products, since many other components in dairy may have impact on CVD risk [ 118 ]. For this reason, more recent studies are also examining novel biomarkers that include vascular function (arterial stiffness, flow-mediated vasodilation (FMD) [ 47 ] and LDL-c particle size distribution [ 119 ]. It is important that we more fully understand the mechanisms underlying the variance in response to consumption, and the use of such novel markers will help develop this knowledge.…”
Section: Conclusion/future Directionsmentioning
confidence: 99%
“…Groups that consumed low-fat or non-fat dairy diet showed decreased levels of TC and LDL cholesterol as compared to the diet containing conventional levels of fat . Most recently, Vasilopoulou et al, (2020) examined the impact of modified dairy fat consumption, through the provision of products with modified MUFA content in adults at moderate CVD risk -the RESET study. The authors concluded that consumption of a high-fat diet containing modified dairy products with reduced saturated fatty acids, and enriched mono unsaturated fatty acids showed beneficial effects on fasting LDL cholesterol and endothelial function compared with conventional dairy products [45].…”
Section: Dairy Fat and Health -Changing Perspectivesmentioning
confidence: 99%
“…Most recently, Vasilopoulou et al, (2020) examined the impact of modified dairy fat consumption, through the provision of products with modified MUFA content in adults at moderate CVD risk -the RESET study. The authors concluded that consumption of a high-fat diet containing modified dairy products with reduced saturated fatty acids, and enriched mono unsaturated fatty acids showed beneficial effects on fasting LDL cholesterol and endothelial function compared with conventional dairy products [45]. Finally, although not an intervention study, Drouin-Chartier (2019), recently examined dairy intake and risk of diabetes, and reported positive impacts for yoghurt and reduced fat milk, but a negative association for cheese [46].…”
Section: Dairy Fat and Health -Changing Perspectivesmentioning
confidence: 99%